The Implementation of Classical Puppet Drama Performance to Improve English Speaking Skill for International Class Program Students - Sari Famularsih (IJORER : International Journal of Recent Educational Research, 2020)
This study analysed the implementation of classical puppet drama performance to improve students’ speaking skill in International Class Program of one of universities in Salatiga. The teaching and learning processes in drama class were(1 ) asking the students with the question, (2) designing drama project plan, (3) creating drama preparation schedules, (4) monitoring the students in preparing the drama, (5) assessing the outcome, and (6) evaluating students’ drama performance. This study was qualitative research in the form of case study. To collect the data the researcher used observation, interview, documentation, and questionnaire. The results showed that by using drama performance, students can improve their pronunciation, fluency, accuracy, handle the voice, and body language to improve their self-confidence to speak in English. Moreover, the used of 4Cs skills activities namely critical thinking, communication, collaboration, and creativity skills in the classroom can stimulate students to improve their group work and interaction among students.